Achilles tendon injuries in high-performance athletes: from tendinopathies to rupture! - de Oliveira Júnior, Otaviano; Martin Marcatti1, Mateus; Medeiros Caetano, Rafael Medeiros Caetano1; Grossi Pereira de Rezende, Rodrigo; Ferrante Rebello de Andrade, Thiago (Journal of the Foot & Ankle, 2024)
Objective: Synthesize the current literature on Achilles tendon injuries, focusing on incidence, risk factors, diagnostic methods, and decision-making among the various treatment options in high-performance athletes. Methods: A search was conducted on PubMed, Scielo, and Scopus databases from 2010 to 2023 using inclusion criteria for studies with athletes and focusing on Achilles tendon injuries. Results: The incidence of Achilles tendon ruptures is approximately 15% among athletes in high-impact sports. Conservative and surgical interventions have shown that individualized treatment plans optimize recovery and prevent the recurrence of injuries. Conclusions: Emerging rehabilitation techniques and surgical interventions have demonstrated a positive impact on the results of returning to sport, offering a comprehensive view of the professionals involved in the care of this group. Level of evidence V; Therapeutic studies - investigating the results of treatment; Expert opinion.